DISSOLUTION RATE ENHANCEMENT OF ATORVASTATIN CA BY ADSORPTION ON MESOPOROUS MATERIAL (SBA-15) SYNTHESIZED AT ROOM TEMPERATURE WITH CHLORIDE SALT ADDITION - Hasanah, Uswatul
Background. Atorvastatin Ca belongs to Biopharmaceuticals Classification System (BCS) class Il which has low solubility in water, approximately 0.02 mg/mL. Mesoporous Silica (SBA-15) has high surface area so it would be able to be employed as adsorbent for the enhancement of dissolution by increasing the contact surface area of atorvastatin Ca with dissolution media. The research aimed to enhance the dissolution rate of atorvastatin Ca with the assistance of SBA-15. Method. SBA-15 was synthetized using PluroniQ on 0.02:166:6:1 molar proportion. Normally, the early step of synthesis should be taken at 35-500 C, but with the addition of 6 mol of salt on surfactant solution, enabling the process to be carried on room temperature. The salts addition were those of inorganic salts: NaCl, KCI, MgC12, and CaC12. SBA-15 was impregnated to atorvastatin Ca solution in methanol with SBA-15:ATV proportion of 1:1 before it was evaporated. The dissolution of atorvastatin Ca which has been adsorbed by the surface of mesoporous silica then tested. Result. The result of synthesis process was SBA-15 in different surface areas, sizes, and pore volumes. The highest surface area achieved by MgC12 addition that was 724.227 m2/g, while the biggest pore size achieved was one by the addition of KCI that was 5.411 nm. The result of dissolution showed the significance enhancement of atorvastatin Ca dissolution after adsorption on SBA-15 surface in comparison with pure atorvastatin Ca. Conclusion. The - dissolution enhancement was proportional to the surface area of SBA-15 excepuhose synthetized using the addition of CaC12, which had smaller pore size.